Brand Image: Strategi Meningkatkan Daya Saing Lembaga Pendidikan - Dian Pratiwi; Afidatul Aniqoh; Agus Suwito; Arga Bayu Pratama; Asa Satmika (Southeast Asian Journal of Islamic Education Management, 2023)
Building a positive image of an educational institution will also impact the institution's ability to compete with other institutions. The strategy of building a brand image certainly plays an important role here. The brand image of an educational institution is essential to maximize the institution's reputation in the minds of the wider community. The research objectives are: 1) To find out the strategies used to build brand image at MAN 2 Ponorogo; 2) To find out how MAN 2 Ponorogo maintains its brand image in competition between educational institutions; 3)To find out the building and influencing factors in the branding process at MAN 2 Ponorogo.The method used in this research is a qualitative research approach with a case study type. The results of this research are focused on the strategies carried out by MAN 2 Ponorogo in building a brand image to increase competitiveness and maintain its brand image in competition between educational institutions by looking at the differences between MAN 2 Ponorogo and other schools so that from these differences a gap emerges for formulate the proper steps.